The Evaluation of Three English Learning Websites - Tahan HJ Sihombing (International Journal of Education, Information Technology, and Others, 2020)
With the growing use of internet, a large number of English learning websites have been developed to assist English learners to improve their English. However, the websites do not always match the learners’ need, learners’ interests, and learners’ characteristic. Hence, it is essential for English teachers to evaluate the English learning websites before they recommend them to their students. The present study evaluated three language learning websites focusing on listening. Three major criteria including design, content, and learner fit were used as the parameters in the present evaluation. It is expected that, upon the evaluation, English language learners can be assisted to choose the best website for their English learning. In addition, this evaluation can contribute to the development of the language learning websites in which the feedback from the evaluation can be incorporated to the better development of the websites.